2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346445
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost, reliable, high-throughput system for rodent behavioral phenotyping in a home cage environment

Abstract: Inexpensive, high-throughput, low maintenance systems for precise temporal and spatial measurement of mouse home cage behavior (including movement, feeding, and drinking) are required to evaluate products from large scale pharmaceutical design and genetic lesion programs. These measurements are also required to interpret results from more focused behavioral assays. We describe the design and validation of a highly-scalable, reliable mouse home cage behavioral monitoring system modeled on a previously described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
7
14
0
Order By: Relevance
“…Our validation tests showed that with no mice in the system, no lick events were observed for any system cage. We also noted excellent agreement in lick events determined by our lickometer compared with manual scoring of high-speed video while a mouse was licking (Parkison et al 2012). The capacitive system easily identifies missed licks (as an electrical connection was not established).…”
Section: Home Cage Monitoringsupporting
confidence: 54%
“…Our validation tests showed that with no mice in the system, no lick events were observed for any system cage. We also noted excellent agreement in lick events determined by our lickometer compared with manual scoring of high-speed video while a mouse was licking (Parkison et al 2012). The capacitive system easily identifies missed licks (as an electrical connection was not established).…”
Section: Home Cage Monitoringsupporting
confidence: 54%
“…Details regarding home cage monitoring (HCM) system design and data analysis algorithms have been described ( Goulding et al, 2008 ; Parkison et al, 2012 ). Briefly, mice are individually housed in low profile (48.3 cm long×25.7 cm wide×15.2 cm high, PC10196HT, Allentown) instrumented cages with ad lib access to food (while breaking a photobeam) and water (while activating a capacitive lickometer).…”
Section: Methodsmentioning
confidence: 99%
“…We employ false discovery rate (FDR) statistics to minimize family-wise error rates; behaviors found significant in this manner are subjected to further analysis. Full details regarding our system hardware and software characteristics have been published (Goulding et al, 2008 ; Parkison et al, 2012 ; Bonasera et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%